Dual effect of reduced type I diacylglycerol kinase activity on insulin secretion from MIN6 β-cells - Toshiaki Sawatani; Yukiko K. Kaneko; Tomohisa Ishikawa (Elsevier, 2019)
The role of type I diacylglycerol kinases (DGKs) in the regulation of insulin secretion was investigated in MIN6 β-cells. In intracellular Ca2+ concentration ([Ca2+]i) measurement experiments, 1 μM R59949, a type I DGK inhibitor, and 10 μM DiC8, a diacylglycerol (DAG) analog, amplified 22.2 mM glucose-induced [Ca2+]i oscillations in a protein kinase C (PKC)-dependent manner, whereas 10 μM R59949 and 100 μM DiC8 decreased [Ca2+]i independent of PKC. High concentrations of R59949 and DiC8 attenuated voltage-dependent Ca2+ channel currents. According to these results, 22.2 mM glucose-stimulated insulin secretion (GSIS) was potentiated by 1 μM R59949 but suppressed by 10 μM of the same. The DGKα inhibitor R59022 showed a similar dual effect. Conversely, DiC8 at 10 and 100 μM potentiated GSIS, although 100 μM DiC8 decreased [Ca2+]i. These results suggest that DAG accumulated through declined type I DGK activity shows a dual effect on insulin secretion depending on the degree of accumulation; a mild DAG accumulation induces a PKC-dependent stimulatory effect on insulin secretion, whereas an excessive DAG accumulation suppresses it in a PKC-independent manner, possibly via attenuation of VDCC activity. Keywords: Diacylglycerol, Diacylglycerol kinase, Insulin secretion, Intracellular Ca2+ concentration, Voltage-dependent Ca2+ channel